Stenotrophomonas maltophilia complex: insights into evolutionary relationships, global distribution and pathogenicity - Li, Kun; Yu, Keyi; Huang, Zhenzhou; Liu, Xiao; Mei, Li; Ren, Xiaodong; Bai, Xuemei; Gao, He; Sun, Zhiwen; Liu, Xiaoning; Wang, Duochun (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction Stenotrophomonas maltophilia complex (Smc) comprises opportunistic Gram-negative bacilli responsible for various nosocomial infections. Limited data exists concerning its evolutionary lineage, global prevalence and pathogenicity. Methods We conducted an extensive genomic analysis on 734 Smc genomes, of which 90 were newly sequenced and isolated from different patients. The species composition and evolutionary relationships of Smc were examined using core protein sequence analysis. Pathogenicity evaluation was used by assays for swimming motility, biofilm formation and identification of virulence factors. The broth microdilution method was used to evaluate the drug resistance spectrum of clinical isolates. Results Phylogenetic analyses delineated 24 species-level clades, dominated by S. maltophilia (42.8%), S. sepilia (13.6%) and S. geniculata (9.9%). Geographically, strains were primarily distributed in Europe (34.2%), Asia (33.7%) and North America (24.0%), with intricate global distribution patterns. Meanwhile, 154 virulence-associated genes and 46 antimicrobial resistance genes within Smc were identified. These genes encoded span various functions, including motility, adherence, toxin, RND antibiotic efflux pumps, beta-lactamases and aminoglycoside-modifying enzymes. Moreover, significant variations were indicated in swimming motility and biofilm-forming capability across the different species, with S. sepilia exhibiting superior levels of both traits. Additionally, no statistically significant discrepancy was detected among Smc species to other antibiotics, despite the fact that all S. geniculata isolates were resistant to Ceftazidime and much higher than other species. Conclusion Our findings indicate the need to pay increased attention to other mainstream species of Smc besides S. maltophilia in order to better manage Smc-related infections and tailor effective treatment strategies.